PROMINENCE OF KNOWLEDGE MANAGEMENT IN INDIAN BIOTECHNOLOGY TRADE - Kumar, Arun; Shekhar, V (PEOPLE: International Journal of Social Sciences, 2017)
Biotechnology is a field which is utterly dependent on knowledge creation and management of novel innovations which are an outcome of contemporary knowledge. Knowledge management is a prime factor which determines the success or failure of a biotechnology company competing in the global competition. A biotechnology company which manages knowledge judiciously will gain commercial value out of the product developed. India is considered to be a hub of Biotechnology industry. With enumerable Biotechnology companies growing in India, knowledge management in this domain has become a matter of utmost prominence. The present work reports the status and prominence of knowledge management in Indian Biotechnology industry. The researcher used the survey method through questionnaire to collect the responses of Biotechnology employees about the present scenario of knowledge management in Indian Biotechnology trade. The study revealed some very interesting facts about knowledge management in Indian Biotechnology sector. The status of knowledge management was totally dependent on the experience of the companies in the market. The middle level management of these companies were well aware of the pros of knowledge management but were negligent towards the proper implementation of knowledge management in Biotechnology companies. 30.7% of the employees opined that their company is recognizing their knowledge but not under the name of knowledge management.25.5% of the surveyed respondents were of the opinion that it’s every individual’s responsibility to manage the knowledge. The employees were also of the opinion that they could acquire the required skills from their colleagues. The study provides an overview and insight about the present scenario of knowledge management in Indian Biotechnology sector. An effective knowledge management model for Indian Biotechnology trade can be thought of as a future research scope.